Diskriminasi Muslim dalam Birokrasi Studi pada Pemerintahan Kota Jayapura - Suparto Iribaram; Irwan Abdullah; Ulung Pribadi (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2018)
This article explains the phenomena of discrimination of Papuan Muslims in the local government in Jayapura Municipality of Papua. In the practice of bureaucracy especially the determination of officials, Papuan Muslims are not involved, even though they are indigenous Papuans. Conditions provide an explanation that there are problems that accompany Muslim travel in Jayapura. This study finds out that of the total 43 units of Regional Working Units (SKPD) which 5 are led by Muslims, while non-Muslims lead others. This composition is unequal of the population in this region, which has a 45% proportion of Protestants and, 41% of Muslims. This paper emphasizes three important points: first, special autonomy for Papua not only affects how regional sentiments are strengthened, but also impacts the treatment of particular groups, especially Muslims. Second, the determination of office in the government is strongly influenced by the similarity of primordial identity, especially ethnicity and religion. Third, from some positions held by Muslims, none of them are from Papuan Muslims.